2003
DOI: 10.1007/s00115-002-1445-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibrat-/Statin-Myopathie

Abstract: Fibrates and statines are useful in preventing arteriosclerosis and thromboembolic events. However, they should be administered with caution. The risk of fibrate/statine myopathy, the most common side effect of fibrate/statine therapy, increases with dosage, combination of a fibrate with a statine,hypothyroidism, renal insufficiency, and intake of cytochrome P450 inhibitors. In case of clinical signs of a fibrate/statine myopathy such as proximal myalgias, stiffness,weakness, and dark urine, appropriate invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
2
Order By: Relevance
“…Rhabdomyolysis as a major statin-associated adverse effect has been reported for all available statins [2] with the highest rate reported for simvastatin [2]. The incidence of clinically relevant rhabdomyolysis is not well defined, but large cohort studies showed incidences of 0.1% [3]. Rhabdomyolysis is defined by creatine kinase (CK) levels at least 10 times normal and reflects acute and massive muscle fiber necrosis accompanied by the release of muscle-related metabolites into the bloodstream [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rhabdomyolysis as a major statin-associated adverse effect has been reported for all available statins [2] with the highest rate reported for simvastatin [2]. The incidence of clinically relevant rhabdomyolysis is not well defined, but large cohort studies showed incidences of 0.1% [3]. Rhabdomyolysis is defined by creatine kinase (CK) levels at least 10 times normal and reflects acute and massive muscle fiber necrosis accompanied by the release of muscle-related metabolites into the bloodstream [4].…”
Section: Introductionmentioning
confidence: 99%
“…Die häufigste symptomatische Manifestation sind Myalgien mit 25 [14]. Neben den Myalgien manifestieren Statin-/ Fibratmyopathien in Form von Muskelkrämpfen, Muskelsteifigkeit, druckdolenter Muskulatur und proximal betonten Paresen [5,8,14,23,24]. Symptomatische Formen können mit und ohne CK-Erhöhung einhergehen [5,14].…”
Section: Statin-/fibratmyopathieunclassified
“…Fibrates and statins are useful in preventing arteriosclerosis and thromboembolic events (8)(9)(10). However, long-term use of these medicines can have side effects, especially when these medicines are used together (8)(9)(10)(11)(12)(13). Therefore, there has been an increasing need to develop medicines derived from herbs with both high effectiveness and safety.…”
Section: Introductionmentioning
confidence: 99%